Participatory research: a catalyst for greater impact - Hellin, Jonathan; Badstue, Lone B.; Bellon, M. (2005)
This paper discusses the notion of farmer empowerment as a primary objective of participatory research. The authors argue that agricultural technologies are adapted - not adopted – through a social and cultural process which includes the transformation of the technology. Farmer participation in agricultural research is important and necessary first of all to increase the efficiency and impact of agricultural research and technology development. This includes the identification of traits that can guide crop breeders’ work. Farmer empowerment is valuable and desirable, and while it can result from participatory research, direct empowerment per se should not be the main objective of participatory research conducted by research organizations. Of more importance is the empowerment of partner organizations and the identification of future research needs, i.e. the functional purposes of participatory approaches in agricultural research.